The barriers to success faced by women in management positions and the mechanisms to overcome them - Verster, Ane (My University, 2017)
The historical background of women in society and the stereotypes around the role and responsibilities of women, are some of the key reasons why women are still underrepresented in management positions within organisations. Women face various challenges in the workplace and this research explored the barriers to success faced by women in management positions and the mechanisms, such as mentorship and education, that they can use to overcome these barriers. The qualitative research method was chosen to complete the study in an attempt to get female individuals’ insights into the current situation women are faced in the workplace. Data was obtained by conducting interviews with 16 female respondents in management and executive positions across the financial services industry, media, consulting, automotive industry, engineering industry and healthcare industry. These interviews were based on a structured questionnaire. The findings in this research where compared to the existing literature. Even though South Africa have implemented gender equality legislation, this research found that there are still various stereotypes that women currently encounter in the workplace which prevents them from advancing to the next level in their careers. The challenges that women face were identified as: gender bias, the underlying culture in organisations, networking, the role females play in an organisation, the payment gap, the glass ceiling effect as well as the Queen Bee syndrome. It was found that mentorship can be used as a mechanism to present future female leaders and allow them to accomplish the required performance, whilst education, such as an MBA, was found not to be helpful to advance women to the next level in their career and specifically in the organisations that the respondents are employed with. This research should be of interest to women who are already or who wants to be in management and executive positions. The researcher set out four suggestions for future research.
MBA Thesis
Keywords: Sex discrimination against women -- South Africa,Women executives,Women -- Employment -- South Africa